Learn Adobe InDesign CC for print and digital media publication : Adobe Certified Associate exam preparation - Gordon, Jonathan (Digital media instructor); Chavez, Conrad; Schwartz, Rob, 1969- (Adobe Press : Pearson Education, 2019)
Used by graphic designers worldwide, Adobe InDesign CC is a layout powerhouse. But that power is easy to harness, as you'll soon learn. These real-world projects teach you to think like a designer and master the details that set your work apart. Hone your InDesign skills as you: Produce an advertising poster Design a magazine for print and tablet delivery Build interactive forms Add controls for video, animations, and more to a digital media publication This study guide uses more than 11 hours of video integrated with text to help you gain real-world skills that will get you started in your career designing publications for print and screen using InDesign CC. It lays the foundation for taking the Adobe Certified Associate (ACA) certification exam and helps prepare you for an entry-level position in a competitive job market. Purchasing this book gives you access to valuable online extras. Follow the instructions in the book's "Getting Started" section to unlock access to: Web Edition containing instructional video embedded in the complete text of the book with interactive review questions along with product updates Downloadable lesson files you need to work through the projects in the book ...